Comprehensive Analysis of Immune Implication and Prognostic Value of IFI44L in Non-Small Cell Lung Cancer - Zeng, Yong; Zhang, Zhe; Chen, Hongqiang; Fan, Jun; Yuan, Wenbo; Li, Jingzhi; Zhou, Shimeng; Liu, Wenbin (Frontiers in Oncology, 2022)
Interferon-induced protein 44-like (IFI44L), a type I interferons-stimulated gene (ISG), has been reported to involve in innate immune process and act as a tumor suppressor in several cancers. However, its immune implication on lung cancer remains unclear. Here we systemically analyzed the immune association of IFI44L with multiple tumor-infiltrating immune cells (TIICs) and immunomodulators through bioinformatics methods in The Cancer Genome Atlas (TCGA) lung cancer cohorts. Then the IFI44L-related immunomodulators were selected to construct the prognostic signatures in lung adenocarcinoma (LUAD) cohort and lung squamous cell carcinoma (LUSC) cohort, respectively. Concordance index and time-dependent receiver operating characteristics curves were applied to evaluate the prognostic signatures. GSE72094 was used to validate the TCGA-LUAD signature. Finally, a nomogram was established by risk score and clinical features in LUAD cohort. The results indicated that IFI44L performed significant correlation with TIICs, no matter in LUAD samples or in the LUSC samples. Functional enrichment analysis showed that IFI44L may participate in various cancer/immune-related pathways, including JAK/STAT signaling pathway and NF-κB signaling pathway. A total of 44 immunomodulators presented obvious association with IFI44L in TCGA-LUAD cohort and a robust 10-immunomodulators signature was constructed. Patients in the higher risk group presented worse prognosis than these in the lower risk group. Notably, the risk signature was successfully validated in GSE72094. Multivariate Cox regression suggested that the risk signature could act as independent prognostic factors both in TCGA-LUAD and GSE72094 cohorts. Besides, a 17-immunomodulators signature was established in TCGA-LUSC cohort and similar results were presented through analysis. The nomogram exhibited good accuracy in predicting overall survival (OS) outcome among TCGA-LUAD patients than the risk signature and else clinical features, with the areas under curve values achieved 0.782 at 1-year, 0.825 at 3-year and 0.792 at 5-year, respectively. Finally, functional experiments found that IFI44L overexpression significantly inhibited the proliferation, migration and invasion in LUAD and LUSC cells. In conclusion, our research highlighted that IFI44L is associated with tumor immune infiltration and provided information of IFI44L’s immune implication, suggesting that the IFI44L is a potential immunotherapeutic target and the proposed nomogram is a promising biomarker for non-small cell lung cancer patients.